A Bibliometric and Visualized Analysis of Uremic Cardiomyopathy From 1990 to 2021 - Bao, Jing-Fu; Hu, Pan-Pan; She, Qin-Ying; Zhang, Difei; Mo, Jia-Ju; Li, Aiqing (Frontiers in Cardiovascular Medicine, 2022)
Background: Uremic cardiomyopathy is commonly presented in chronic kidney disease (CKD), and it severely affects the prognosis of patients with CKD. In the past few decades, the investigation on uremic cardiomyopathy has developed rapidly. However, no report has summarized the situation of uremic cardiomyopathy research to date. This study aimed to evaluate the current state of uremic cardiomyopathy research in the last 35 years and identify important topic, achievements, as well as emerging trends via bibliometric analysis. Methods: Publications related to uremic cardiomyopathy were collected from Web of Science Core Collection. HistCite, VOSviewer, CiteSpace, and the Bibliometrix Package were used for bibliometric analysis and visualization, including the analysis of the overall distribution of annual publication, leading countries, active institutions and authors, core journals, co-cited references, and keywords. Results: A total of 3,078 papers related to uremic cardiomyopathy were obtained, progress related to uremic cardiomyopathy was slower in past three years. A total of 12,918 authors from 3,279 institutions in 95 countries reported investigations on uremic cardiomyopathy. The United States of America was the most productive and the most cited country. Myles Wolf, Carmine Zoccali, and Joseph I Shapiro published most articles in uremic cardiomyopathy, and journals in nephrology possessed core status in the field. Phosphate metabolism was the hotspot in uremic cardiomyopathy research, and future progress may concentrate on biomarkers, phosphate metabolism, and obstructive sleep apnea. Conclusion: Global publications on uremic cardiomyopathy have entered platform stage, and novel breakthroughs were required. Chinese scholars should demonstrate a greater level of involvement in uremic cardiomyopathy field, with the aid of ample clinical resources.